The role of a defunctioning stoma for colonic and perianal Crohn's disease in the biological era - Martí-Gallostra, M; Myrelid, P; Mortensen, N; Keshav, S; Travis, S; George, B (Taylor and Francis, 2016)
OBJECTIVE: A defunctioning stoma is a therapeutic option for colonic or perianal Crohn's disease. In the pre-biologic era the response rate to defunctioning in our unit was high (86%), but intestinal continuity was only restored in 11-20%. Few data exist on the outcome of defunctioning since the widespread introduction of biologicals. MATERIAL AND METHODS: All patients undergoing a defunctioning stoma for colonic/perianal Crohn's disease since 2003-2011 were identified from a prospective database. Indications for surgery, medical therapy, response to defunctioning and long-term clinical outcome were recorded. Successful restoration of continuity was defined as no stoma at last follow up. RESULTS: Seventy-six patients were defunctioned (57 with biologicals) and at last follow up, 20 (27%) had continuity restored. Early clinical response rate (<3 months) was 15/76 (20%) and overall response 31/76 (41%). Complex anal fistulae/stenosis were associated with a very low chance of restoring continuity (10% and 0%, respectively), while colitis was associated with a higher chance of restoring continuity (48%). Endoscopic or histological improvement in colitis after defunctioning was associated with a higher rate of restoring continuity (10/16, 63%) compared to no such improvement (4/15, 27%, p = 0.05). Those failing biologics had similar chance of restoration as those not receiving biologics, 15/57 (26%) and 5/19 (26%), respectively. CONCLUSION: Overall response to colonic defunctioning was 41%. Successful restoration of continuity occurred in 27%, but 48% in the absence of perianal disease. Response is appreciably less in the pre-biologic era, so patient and physician expectations need to be managed appropriately.